PELANGGARAN MAKSIM KUANTITAS MENCIPTAKAN HUMOR DAN IRONI DALAM NOVEL “DAN HUJAN PUN BERHENTI” KARYA FARIDA SUSANTY - Tamara, Dwinda (Faculty of Letters Universitas Balikpapan, 2025)
Cooperative principles in conversation violation can occur in any situation or context, especially conversations involving two persons. Speakers tend to be uncooperative because they always try to explore various topics to communicate further. Questioners or listeners usually find it difficult to get the meaning of the speaker in such situations. In order to avoid misunderstandings and misinterpretations between the speaker and questioner or listener, both the speaker and questioner or listener must have a cooperative attitude. In this research, the author examines about violation of quantity maxim in a novel entitled Dan Hujan pun Berhenti by Farida Susanty. The aim of this study was to determine what is the reason of quantity maxim violations and defense mechanism usage as background why characters in the novel violate quantity maxim that occur in the novel dialogue. The research’s data were the dialogues of the Dan Hujan pun Berhenti’s characters that violate the cooperative principle in conversation that will be analyze by using qualitative descriptive paradigm based on Grice’s cooperative principle, Cook’s maxim violation and Freud’s defense mechanism. The results of this study state the defense mechanism as background that causes characters in the novel violates quantity maxim: reaction formation, displacement and repression.